Tackling food loss in Vietnam Logistics sector VIA technology - Tang, Minh Huong; Ho, Thi Thu Hoa; Do, Doan Trang; Nguyen, Quynh Phuong; Nguyen, Quynh Lam; Vo, Trong Cang (Tập san Khoa học và kỹ thuật trường Đại học Bình Dương, 2022)
Food loss in Vietnam is a major concern for the government, commercial sector, and regulators, and many others. Food loss is exacerbated during epidemics, when the supply chain is disrupted, border crossings are blocked, aircraft are restricted, etc., necessitating the state and enterprises to develop policies and effective ways to address this problem. There are already numerous firms in Vietnam that have excellent solutions for dealing with food loss, and employing technology is one of the most effective ways for businesses to control food loss and drastically reduce the rate of food loss throughout the food supply chain. The article will analyze technology solutions used by Vietnamese enterprises to prevent food loss, as well as existing and potential technologies around the world that can help to lessen food loss.